2020
DOI: 10.1016/j.biochi.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system at the heart of COVID-19 pandemic

Abstract: Significant aspects of COVID-19 pandemic remain obscure. Angiotensin converting enzyme 2 (ACE2), a component of the renin-angiotensin system, whose expression dominates on lung alveolar epithelial cells, is the human cell receptor of SARS-CoV-2, the causative agent of COVID-19. We strongly encourage the concept that thorough considerations of receptorligand interactions should be kept at the heart of scientific debate on infection. In this idea, the whole renin-angiotensin system has to be evaluated. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
149
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(156 citation statements)
references
References 25 publications
1
149
0
6
Order By: Relevance
“…On the other hand, it has been hypothesized that, regardless of sex, pharmacological (antihypertensive drugs, such as ACE inhibitors and sartans) or environmental factors (NO2 pollution), capable of inducing an overexpression of ACE2 could be responsible of increased susceptibility to infection and/or greater severity 47 . ACE2 plays an essential role in the renin-angiotensinaldosterone system, and its loss of function due to the massive binding of viral particles and internalization could constitute an essential element of the pathophysiology of pulmonary and cardiac damage during COVID-19 infection 47,48 . In this context it should be underlined that ACE2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been hypothesized that, regardless of sex, pharmacological (antihypertensive drugs, such as ACE inhibitors and sartans) or environmental factors (NO2 pollution), capable of inducing an overexpression of ACE2 could be responsible of increased susceptibility to infection and/or greater severity 47 . ACE2 plays an essential role in the renin-angiotensinaldosterone system, and its loss of function due to the massive binding of viral particles and internalization could constitute an essential element of the pathophysiology of pulmonary and cardiac damage during COVID-19 infection 47,48 . In this context it should be underlined that ACE2…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that polymorphisms in the ACE2 gene could reduce the spike affinity, with subsequent lower susceptibility to infection: in this hypothesis, their geographical / ethnical distribution could explain the strong discrepancies in infection rate and/or lethality observed worldwide 47 . Effectively, we showed by Network plot and Non-Metric Multidimensional Scaling that most of the SNPs diffused worldwide did not affect significantly the interaction of ACE2 with SARS-CoV-2 Spike.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus infection did not differ: obese patients have been associated with a higher risk of morbidity and mortality. Several reasons for the increased lethality of COVID-19 infection have been advanced going from the uncontrolled inflammatory cascade leading to and/or aggravating acute respiratory failure, the overexpression of ACE2-at the heart of the debate on the COVID-19 pandemic [4]-in adipose tissue, and the metabolic obesity-related comorbidities, namely type 2 diabetes and hypertension that have been shown to be associated with increased disease severity and mortality [5,6]. However, deregulation of the renin/ angiotensin system in obese patients warrants some consideration.…”
mentioning
confidence: 99%
“…In this line, the expression of ACE2 is also inter-regulated by immune mediators pertinent to its systemic function. Multiple physio-pathological factors, including pathogenic inflammation, influence on RAS through action on ACE2 expression [29][30][31]. Interferon (IFN) response, especially that mediated by type I and type III IFNs, comprises a frontline of antiviral immunity to restrict viral spreading from the initial infection sites, and therefore primarily determines if a viral exposure becomes controlled or a productive infection [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies revealed that human ACE2 gene behaves like an interferon-stimulated gene (ISG) and is stimulated by a viral infection and IFN treatment; however, mouse ACE2 gene is not [15,33,34]. Therefore, to determine the cell tropism and animal susceptibility to SARS-CoV2, the cross-species ACE2 genetic and especially epigenetic diversity in regulation of ACE2 expression and functionality should be evaluated [26][27][28][29][30][31][32][33][34]. In this study, through integration of structural analysis and key immunogenetic factors that show species-dependent differences, we critically refine the SARS-CoV2 susceptibility prediction to fit recent experimental validation [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%